Analisis Permasalahan Siswa Kelas 1 SD Ta`mirul Islam Inovatif dalam Melaksanakan Pembelajaran - Mardhiyah, Dini (Universitas Sebelas Maret, 2022)
Education in schools plays a crucial role in shaping human development. Students undergo a structured and consistent learning process from Kindergarten to tertiary institutions, establishing a solid foundation for acquiring essential knowledge. Elementary school education serves as a fundamental pillar, enabling individuals to progress to higher levels of education and fostering proper development within society. This research employs descriptive qualitative methods, utilizing literature reviews, observations, interviews, and documentation for data collection. Various research instruments, including observation papers, interview guides, books, and scientific articles, contribute to the comprehensive analysis. The chosen research method aligns with the study's objective, aiming to depict prevailing conditions and identify solutions to challenges faced by early elementary school students, particularly grade 1 students at SD Ta`mirul Islam Inovatif. The study revealed issues such as a lack of motivation, difficulties in social interaction, and challenges in retaining learned information, including test and class schedules. Additionally, the research proposes several solutions that may offer insights for educators and parents facing similar issues